Effects of Climate Change vs. Grazing Exclusion on Species Diversity Over 18 Years Along an Elevation Gradient in the European Alps - Kaufmann, Rüdiger; Mayer, Roland; Schallhart, Nikolaus; Erschbamer, Brigitta (Frontiers in Ecology and Evolution, 2021)
Background: Climate change as well as grazing are essential drivers of species diversity in high elevations. However, grazing might interfere with climate change effects. It remains a major challenge of alpine ecology to disentangle both the effects. Our long term study will contribute to this topic. Questions: How do species diversity and frequency of subalpine-alpine-subnival plant communities change in grazed sites with time? Do competitive plant species increase in the communities? How does grazing exclusion affect species diversity, functional groups and strategy types? Are environmental changes (temperature, sunshine duration, precipitation) responsible for diversity changes or does grazing override climate effects? Material and Methods: The study was carried out for 18 years along a gradient from 1958 m to 2778 m a.s.l. at Obergurgl (Tyrol, Austria). At each site, the frequency of the species was counted in 1 m² plots yearly or at least every three to four years. Environmental data were obtained from the weather station Obergurgl. Changes of the community parameters and the species composition were analysed by partial redundancy analyses and mixed effect models. Main Results: Species diversity increased with time at all grazed sites, but this increase was suppressed under grazing exclusion. Grazing exclusion effects became pronounced after 5 years. The most consistent result was the increase of bryophytes throughout. At the subalpine grassland, tall-growing species expanded in the exclosures; at the upper alpine Carex curvula grassland snow bed species decreased with grazing exclusion. Among the environmental factors, sunshine duration of the previous year’s autumn quartal was found to be the essential variable for the changes. Conclusion: Diversity increases in grazed communities of the Central Austrian Alps were attributed to climate change. An indication of slightly reduced and altered weather effects under grazing exclusion was found.